BIOLOGICAL ACTIVITY OF PLANTS OF THE GENUS NITRARIA (Scientific journal of the Fergana State University, 2024)
The article presents the results of studying the biological activity of plants of the genus Nitraria. The distribution, phylogeny and systematics of the family Nitrariaceae are described in detail. The biological activities of Nitraria retusa, Nitraria tangutorum and Nitraria schoberi are discussed in detail.